Kajian Kepatuhan Terapi dan Kualitas Hidup Terkait Kesehatan Pasien DM Tipe II di Poli Penyakit Dalam RSUD HA Thalib Kota Sungai Penuh - Rizqaini, Alfitratul; Muharni, Muharni; Restusari, Lily; Rahayu, Dewi (Poltekkes Kemenkes Riau, 2025)
Chronic Energy Deficiency (CED) is a condition of long-term undernutrition in pregnant women, indicated by a mid-upper arm circumference (MUAC) of less than 23.5 cm, and poses risks to both maternal and fetal health. One of the government strategies to address this issue is the provision of locally based supplementary food (Local Supplementary Feeding). However, most previous studies have predominantly employed quantitative approaches and focused on program coverage, while in-depth case-based analyses at the primary health care level remain limited. This study aimed to describe changes in the nutritional status of pregnant women with CED before and after receiving Local Supplementary Feeding in the working area of Pekanbaru City Primary Health Center in 2024. A qualitative approach with a descriptive case study design was applied to three pregnant women with CED from August 2024 to May 2025. Data were collected through interviews and secondary data from the e-PPGBM system. The results showed an increase in body weight ranging from 5.5 to 12.95 kg and an increase in MUAC of 1–2 cm. However, one case of low birth weight was still observed, indicating the need to evaluate the quality and effectiveness of Local Supplementary Feeding interventions.